The figure of the mentor in the training of novice teachers (Journal of Parents and Teachers, 2023)
The initiation to teaching is often accompanied by a huge number of insecurities. To address these insecurities, the role of the mentor is essential to make the beginning easier. In addition to supervising, this mentor will help the young teacher to be able to reflect on education, but will have a number of requirements if we want the training model to be effective.
Keywords: teachers; education; mentor